2019
DOI: 10.1007/978-3-030-14227-8_3
|View full text |Cite
|
Sign up to set email alerts
|

New Tools in Education: Development and Learning Effectiveness of a Computer Application for Use in a University Biology Curriculum

Abstract: translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Online gamification platforms will be used increasingly as digital tools in the medical education. 6,10,11 The enormous digital innovations in medicine will produce new powerful opportunities for medical education. Additionally, it could be empirically demonstrated that gaming may be more effective than traditional teaching methods 12,13 due to increased student motivation and engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Online gamification platforms will be used increasingly as digital tools in the medical education. 6,10,11 The enormous digital innovations in medicine will produce new powerful opportunities for medical education. Additionally, it could be empirically demonstrated that gaming may be more effective than traditional teaching methods 12,13 due to increased student motivation and engagement.…”
Section: Discussionmentioning
confidence: 99%
“…9 Additional investigations have shown that game-based learning has several benefits compared to conventional teaching methods. 10,11 Indeed, including the concept of gamification in medical teaching could increase the motivation of the students and subsequently significantly improve learning behavior. 12,13 Today, a number of software platforms are available to gamificate the course contents through online applications such as Kahoot!, Quizziz, Quizlet, and Socrative.…”
Section: Introductionmentioning
confidence: 99%
“…As such, software education is gradually expanding, and studies on teaching methods, learning methods, and effectiveness verification are actively being conducted, but studies on evaluation are relatively insufficient [2] - [5]. Since cultivation of computational thinking is the ultimate purpose of software education, although how to evaluate the improvement of computational thinking is a very important issue, the research on this is relatively incomplete [6] - [10].…”
Section: Introductionmentioning
confidence: 99%